Autoprothrombin C Activity from Prothrombin with Snake Venom or Trypsin - Marciniak, Ewa; Cole, Edmond R; Seegers, Walter H (Thrombosis and Haemostasis, 1962)
Suitable conditions were found for the generation of autoprothrombin C from purified prothrombin with the use of Russell’s viper venom or trypsin. DEAE chromatographed prothrombin is structurally altered and has never been found to yield autoprothrombin C and also did not yield it when Russell’s viper venom or trypsin were used. Autoprothrombin C is derived from prothrombin with tissue extract thromboplastin, but not in large amounts with the intrinsic clotting factors. With the latter thrombin and autoprothrombin III are the chief activation products. Autoprothrombin III concentrates were prepared from serum and upon activation with 25% sodium citrate solution or with Russell’s viper venom large amounts of autoprothrombin C were obtained, and this was of high specific activity. Theoretically trypsin is not a thrombolytic agent, but on the contrary should lead to intravascular clotting.